Oxford Handbook of Urology, 1st Edition - Reynard, John, Brewster, Simon; Biers, Suzanne (OXFORD UNIVERSITY PRESS, 2006)
Oxford Handbook of Clinical Medicine 6/e Oxford Handbook of Clinical Specialties 6/e Oxford Handbook of Accident and Emergency Medicine 2/e Oxford Handbook of Acute Medicine 2/e Oxford Handbook of Anaesthesia Oxford Handbook of Applied Dental Sciences Oxford Handbook of Clinical and Laboratory Investigation Oxford Handbook of Clinical Dentistry 3/e Oxford Handbook of Clinical Genetics Oxford Handbook of Clinical Haematology 2/e Oxford Handbook of Clinical Immunology Oxford Handbook of Clinical Surgery 2/e Oxford Handbook of Critical Care Oxford Handbook of Dental Patient Care Oxford Handbook of Dialysis 2/e